Scientific cooperation of the teaching staff to guide investigations of the Master's Degree in public health of the Faculty of Medicine - Mazariego Flores, Edwin (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
This study is a fragment of another document that has resulted from a doctoral thesis in higher education where, having initially determined the variable "scientific cooperation of the teaching staff for the tutorial orientation of the research of the master's degree in public health of the Faculty of medicine", its dimensions and its indicators, the parameters and its decision rules; When analyzing and interpreting the data obtained, it is concluded that: Scientific cooperation for the tutorial orientation of research in the master's degree in public health, averaging the results of tutors and tutors, is established at x̄ 3.7, Moderately frequent: occurs between 41 and 60% of the shares. Therefore, and taking into account the qualitative criteria provided by the research subjects, the need for the implementation of a scientific cooperation strategy for the tutorial orientation of research to improve training in the context of the Master in Health is affirmed in the Faculty of Medicine of the University of El Salvador.